PENGARUH FAKTOR – FAKTOR MARKETING MIX TERHADAP NIAT BELI DI HYPERMARKET DENGAN PERSEPSI NILAI KONSUMEN SEBAGAI VARIABEL MEDIASI - Dodi Riatmaja (STIESNU Bengkulu, 2018)
This research is trying to express the influence of marketing mix which is represented by the variable product, price, place and promotion of consumer spending intentions in the retail industry in Indonesia. Conditions retail Industry is currently entering a very tight competition conditions, where so many businesses in this sector to encourage management develop marketing strategy of what needs to be prioritized and seeded as a competitive advantage. The study began with a pretest and continued to examine the 200 respondents’ customers a modern market outlet in Jakarta. This study answered clearly that in addition the marketing mix, especially products will increase consumer value perception. Obtained from the results, expected future studies will further enrich the study of the marketing mix. Keywords: marketing mix, retail, competitive, modern market, perception